Vapor-Liquid Equilibrium Prediction of Ammonia-Ionic Liquid Working Pairs of Absorption Cycle Using UNIFAC Model - 孙光明 黄维佳 郑丹星 董丽 武向红 (Chinese journal of chemical engineering, 2014)
On the basis of reported experimental vapor-liquid equilibrium （VLE） data of NH3-1-ethyl-3-methylimidazolium acetate （NH3-[Emim]Ac）, NH3-1-butyl-3-methylimidazolium tetrafluoroborate （NH3-[Bmim][BF4]）, NH3-1,3-dimethylimidazolium dimethyl phosphate （NH3-[Mmim]DMP） and NH3-1-ethyl-3-methylimidazolium ethylsulfate （NH3-[Emim]EtOSO3） binary systems, the interaction parameters of 14 new groups have been regressed by means of the UNIFAC model. To validate the reliability of the method, these parameters have been used to calculate the VLE data with the average relative deviation of pressures of less than 9.35%. The infinite dilution activity coefficient （ γ1∞ ） and the absorption potential （ φ1 ） are important evaluation criterions of the affinity between working pair species of the absorption cycle. The UNIFAC model is implemented to predict the values of and φ1 of t6 sets of NH3-ionic liquid （1L） systems. The work found that the φ1 gradually increases following the impact order： φ1（[Cnmim][BF4]）〈φ1（[Cnmim]EtOSO3）〈φ1（[Cnmim]DMP）〈φ1（[Cnmim]Ac） （n= 1, 2, 3, … ） at a given cation of IL species and constant temperature, and φ1（[Mmim]X）〈φ1（[Emim]X）〈φ1（[Pmim]X）〈 φ1（[Bmim]X）（X= Ac, [BF4], DMP or EtOSO3） at a given anion of IL species and constant temperature. Furthermore, the φ1 gradually increases with increasing temperature. Then, it could be concluded that the working pair NH3-[BmimlAc has the best potential research value relatively.